Inhibition of the left medial prefrontal cortex (mPFC) prolongs the social defeat-induced anxiogenesis in mice: Attenuation by NMDA receptor blockade in the right mPFC - Victoriano, Gabriel [UNESP]; Santos-Costa, Nathália [UNESP]; Mascarenhas, Diego Cardozo [UNESP]; Nunes-de-Souza, Ricardo Luiz [UNESP] (Elsevier, 2020)
Chemical inhibition and nitrergic stimulation of the left and right medial prefrontal cortex (L and RmPFC), respectively, provoke anxiety in mice. Moreover, LmPFC inhibition immediately followed by a single social defeat stress (SDS) led to anxiogenesis in mice exposed to the elevated plus maze (EPM) 24 h later. Given that glutamate NMDA (N-methyl-D-aspartate) receptors are densely present in the mPFC, we investigated (i) the time course of LmPFC inhibition + SDS-induced anxiogenesis and (ii) the effects of intra-RmPFC injection of AP-7 (a NMDA receptor antagonist) on this long-lasting anxiety. Male Swiss mice received intra-LmPFC injection of CoCl2 (1 mM) and 10 min later were subjected to a single SDS episode and then (i) exposed to the EPM 2, 5, or 10 days later or (ii) 2 days later, received intra-RmPFC injection of AP-7 (0.05 nmol) and were exposed to the EPM to observe the percentage of open arm entries and time (%OE; %OT) and frequency of closed arm entries (CE). Dorsal but not ventral LmPFC inhibition + SDS reduced open arm exploration 2, 5, and 10 days later relative to that of saline-treated or non-defeated mice. Moreover, this effect is not due to locomotor impairment as assessed using the general activity. Intra-RmPFC AP-7 injection 2 days after LmPFC inhibition + SDS prevented this type of anxiogenesis. These results suggest that the integrity of the LmPFC is important for mice to properly cope with SDS, and that NMDA receptor blockade in the RmPFC facilitates resilience to SDS-induced anxiogenesis in mice.
Keywords: Anxiety; Elevated plus-maze; Glutamate NMDA receptors; Left and right medial prefrontal cortex; Mice; Social defeat stress